Etika Komunikasi Bisnis dalam Strategi Pemasaran Produk Bertani Agro Farm di Media Sosial Instagram - Wibowo, Ghina Nasywa; Prayoga, Kadhung; Roessali, Wiludjeng (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Marketing strategies through social media, especially Instagram, are currently one of the main choices for business actors in promoting products. This study was conducted with the aim of understanding how the principles of business communication ethics are applied in Bertani Agro Farm's marketing strategy on Instagram. The study was conducted for one month, from April to May 2025, with a qualitative approach and supported by quantitative data. Data were obtained through observation, interviews with the owner of Bertani Agro Farm, documentation, and consumer perceptions who are followers of the Bertani Agro Farm Instagram account. The validity of the data was tested through source triangulation, while the analysis was carried out descriptively-qualitatively. These findings are expected to be a reference for business actors in developing ethical marketing strategies in promotional content. However, two-way communication still needs to be improved. Business communication ethics have been shown to play a role in building consumer trust and loyalty, making it an essential strategy in digital marketing. This study is expected to be a reference for business actors in developing ethical marketing strategies.